Kontribusi Self-Regulation dan Konformitas Teman Sebaya terhadap Prokrastinasi Akademik Siswa Kelas VIII SMP Negeri 25 Banjarmasin - Sulaiman, Muhammad Agus; Sulistiyana, Sulistiyana; Makaria, Eklys Cheseda (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
The phenomenon that occurs at this time, students tend to spend their time on entertainment matters only compared to academic matters, this is a problem for students who like to delay doing school work. Academic procrastination may continue to increase each year, therefore this study aims to determine the picture of self-regulation, peer conformity, and academic procrastination, as well as to determine the contribution between self regulation and peer-to-peer conformity to academic procrastination using quantitative approaches with this type of contribution research. The data collection tool used a series and the sampling technique was simple random sampling. So there are 98 students of class VIII SMP Negeri 25 Banjarmasin as the research sample. Data analysis techniques use descriptive statistics, simple linear regression, and multiple linear regression. The results of the study stated that grade VIII students had moderate academic self-regulation and procrastination, while peer conformity was in the high category. Then the results of the study stated that there was a contribution between self-regulation and peer conformity to academic procrastination with a value of sig 0.000 <0.05. In other words, students who have moderate self-regulation and high peer conformity in students will tend to do academic procrastination.